2016
DOI: 10.1590/1676-0611-bn-2015-0132
|View full text |Cite
|
Sign up to set email alerts
|

List of Odonates from the Floresta Nacional de São Francisco de Paula (FLONA - SFP), with two new distribution records for Rio Grande do Sul, Brazil

Abstract: A survey of Odonata was carried out in the National Forest FLONA - SFP, Northeastern region of the Rio Grande do Sul state, Brazil. This conservation unit is mainly covered by Mixed Ombrophilous Forest (MOF), a subtype of Atlantic Forest biome, being also areas covered in planted Pinus, planted Araucaria and open fields. Our sampling efforts were conducted in thirty aquatic environments inside this reserve during the period between January 2014 and November 2014. The sampling sites were selected randomly, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…In addition, 30 species were exclusive of farm ponds (Table 2). The higher number of exclusive species in farm ponds was also detected in other regions of southern Brazil (Renner et al 2016b). Previous reviews showed that man-made farm ponds can increase the regional pool of species richness, mostly by acting as an additional habitat for generalist species (Ruggiero et al 2008).…”
Section: Odonate Assemblages In Farm Ponds and Streamsmentioning
confidence: 60%
“…In addition, 30 species were exclusive of farm ponds (Table 2). The higher number of exclusive species in farm ponds was also detected in other regions of southern Brazil (Renner et al 2016b). Previous reviews showed that man-made farm ponds can increase the regional pool of species richness, mostly by acting as an additional habitat for generalist species (Ruggiero et al 2008).…”
Section: Odonate Assemblages In Farm Ponds and Streamsmentioning
confidence: 60%
“…Even with important taxonomists in the recent Brazilian history, odonates are still poorly described and its distribution is deficiently known in the Neotropical region (Kalkman et al 2008). Local inventories are recorded to several parts of Brazil like São Paulo (Costa et al 2000), Espirito Santo (Costa & Oldrini 2005), Rio de Janeiro (Anjos-Santos & Costa 2006), Goiás and Distrito Federal (Nóbrega & De Marco 2011), Minas Gerais (Souza et al 2013), and Rio Grande do Sul (Renner et al 2016). In Mato Grosso do Sul, state originally covered by Cerrado,Pantanal,Atlantic Forest and Chaco vegetation,198 odonatan species were registered (Rodrigues & Roque 2017).…”
Section: Introductionmentioning
confidence: 99%
“…If this pattern is confirmed in future studies, it would mean that human alteration of habitats may reduce the evolutionary potential in this polymorphic species (see [24]. The genus Argia constitutes an indicator of environmental quality [43][44][45][46] and the analysis of its intraspecific variability could enrich these assessments [47,48]. Due to their colour and behavioural similarities with males, androchromes might avoid male harassment and therefore be favoured if male density increases [49,50] under a negative frequency-dependent selection (e.g.…”
Section: Discussionmentioning
confidence: 99%